Access to knowledge through mobile devices by university students - Montúfar Flores, Manuel Alfredo; Rosero Ortega, Viviana Estefanía; Tulcán Guamán, Jenniffer Jacqueline; Veloz Piarpuezan, Maryory Lisbeth (SATHIRI, 2020)
The objective of this research was to analyze access to knowledge through mobile devices by university students. The scientific research methodology used for the Carchi State Polytechnic University case was Bibliographic, Descriptive and Field, which through the survey technique managed to collect data that allowed us to know what the incidence is generated by the use of Information Technologies and Communication (ICT) in the practice of digital university education. From the academic field and the Binational Border Observatory, it is concluded that access to the mobile resource enables the transfer of knowledge, virtual learning and professional success; However, it is necessary to motivate the desire to learn in students, since the proper use of mobile computers facilitates the academic training process, saves time and optimizes digital resources in favor of students.